ANALISIS EROSI DAN TEKNIK KONSERVASI LAHAN PADA DAERAH ALIRAN SUNGAI (DAS) WAERUHU KOTA AMBON - , HERFIEN SAMALEHU ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Increased demand for land has become a trigger of land conversion in the Waeruhu watershed uncontrolled and without considering the area function is utilized or the carrying capacity of land that serves as a water catchment area in the upper reaches. In addition, the sedimentation in the Gulf has led to silting of the Baguala bay who threaten disruption of the balance in the marine ecosystem. This study aims to calculate and analyze the amount of erosion that occurs in the Waeruhu watershed as soil conservation measures using USLE and MUSLE Methods by Snyder, 1981. The method of research includes literature review, data collection, data processing and analysis, including the calculation of the rate of erosion using USLE and MUSLE Methods, Erosion hazard level classification (TBE), the value of Sediment Delivery Ratio (SDR), the direction of land use, as well as erosion control measures and land conservation technique. The results showed erosion in the Waeruhu watershed existing condition based on USLE method is 124,773.65 tons / year or equivalent to 114.98 tons / ha / year, while based method musle is 142,201.23 tons / year or equivalent to 131.04 tons / ha / year. The largest contributor to erosion in the Waeruhu watershed was the land use of Cultivated land with the total of erosion is 36,911.47 to 46,501.53 tons/year. Erosion hazard classification in Waeruhu watershed is classified into erosion of class III (moderate) which is equivalent to the loss of soil thickness of 6.39 â 7.28 mm/year. After the land conservation efforts, the amount of erosion that occurs in the watershed has decreased at a rate Waeruhu erosion by USLE Method to 30,727.39 tons/year or 28.31 tons/ha/year, while the rate of erosion based on MUSLE method reduced to 60,116.83 tons/year or equivalent to 55.40 tons/ha/year. Conservation and erosion control is conducted as vegetative, changes in terrace, reproducing canopy closure in plants and crop setting efforts with the result that the vegetation density levels will be the better afterwards.